Pengaruh Fasilitas Perpustakaan terhadap Minat Baca Siswa di Perpustakaan MAN Curup Rejang Lebong - Rizkyantha, Okky; Tamalah, Dipi; Iswanto, Rahmat (Prodi Ilmu Perpustakaan dan Informasi Universitas Islam Negeri Raden Fatah Palembang, 2022)
The purpose of this study was to determine library facilities, the level of interest in reading and the effect of limited library facilities on students' reading interest at MAN Curup Rejang Lebong. This study used a quantitative research approach which showed the effect of variable X on variable Y. The population in this study were 541 students of MAN Curup Rejang Lebong. The sample in this study was 54 people or 10%. Data collection techniques used are observation, questionnaires and documentation. While technical data analysis using descriptive statistical analysis and inferential statistical analysis techniques using Simple Linear Regression. With the results of the study showing that the library facilities in Curup Rejang Lebong MAN were in the good category with a percentage rate of 79.80 percent. The reading interest level of students at MAN Curup Rejang Lebong is in the high category with a percentage rate of 79.76 percent. This can be proven by the results of simple linear regression, namely the results obtained f count> f table, namely 71.300> 4.08, then Ho is rejected and Ha is accepted. So it can be concluded that there is an influence of library facilities on students' reading interest at MAN Curup Rejang Lebong.